2008
DOI: 10.1351/pac200880051005
|View full text |Cite
|
Sign up to set email alerts
|

New synthetic methodologies based on active transition metals

Abstract: Active transition metals, namely, nickel, copper and iron, have been prepared by the reduction of the corresponding chlorides with lithium and a catalytic amount of an arene. These metals, in the form of nanoparticles, have found application in the reduction of a wide variety of functional groups as well as in the alkylation of methyl ketones with primary alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The methodology of Alonso’s group [ 21 ] was applied for the synthesis of CuNPs/TiO 2 . In this protocol, a suspension was prepared in a Schlenk flask containing lithium powder (14 mg, 2.0 mmol, Medalchemy S.L.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of Alonso’s group [ 21 ] was applied for the synthesis of CuNPs/TiO 2 . In this protocol, a suspension was prepared in a Schlenk flask containing lithium powder (14 mg, 2.0 mmol, Medalchemy S.L.)…”
Section: Methodsmentioning
confidence: 99%
“…We have been involved in the development of methods to prepare metal nanoparticles [ 21 ], copper nanoparticles among them [ 22 ], which have found application as chemical catalysts either unsupported [ 23 ] or supported on a variety of inorganic supports, including zeolite Y [ 24 ], charcoal [ 25 ], and titania [ 26 ]. A previous comparison of CuNPs of different size, morphology, and inorganic support enabled us [ 20 ] to identify CuNPs supported on titania nanopowder (CuNPs/TiO 2 ) as a nanoparticle combination with a potent direct effect on ovarian cells.…”
Section: Introductionmentioning
confidence: 99%
“…CuNPs are largely obtained by wet chemical synthesis, electrochemical and biosynthesis. In wet chemical synthetic method, the Cu salt are reduced with suitable reducing agent that provide electrons for the reduction of Cu atom, which includes reducing agents such as NaBH 4 ,, NH 2 ‐NH 2 ,, metal Li, ascorbic acid etc. Biosynthesis of CuNPs is also involves the reduction of Cu salts, especially CuCl 2 , CuSO 4 etc., In this method, the source of reducing agent for reduction is either plant extracts, bacteria or fungus .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have previously shown that Cu NPs could be formed either from CuCl 2 $2H 2 O or anhydrous CuCl 2 and elemental lithium in the presence of catalytic 4,4 0 -ditert-butylbiphenyl (DTBB) in THF at room temperature. 13,19 These Cu NPs effectively catalysed the 1,3-dipolar cycloaddition of organic azides and terminal alkynes in remarkably short reaction times (10-120 min). 13,23 Notwithstanding the superior catalytic activity observed when we compared these systems with other commercially available copper sources, the Cu NPs underwent dissolution under reaction conditions (Et 3 N, THF, 65 C) and could not be reused.…”
Section: Introductionmentioning
confidence: 99%